2019
DOI: 10.7748/ns.2019.e11362
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the benefits and risks of nursing students engaging with online social media

Abstract: Where a licence is displayed above, please note the terms and conditions of the licence govern your use of this document. When citing, please reference the published version. Take down policy While the University of Birmingham exercises care and attention in making items available there are rare occasions when an item has been uploaded in error or has been deemed to be commercially or otherwise sensitive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…To facilitate this, sectors like pharmacy and dentistry have seen a growth in research into the issues surrounding digital professionalism [13,14]. The skills and professionalism required by nurses engaging online has more recently been explored [15,16], and training introduced to pre-registration programmes [17]. However, there is reluctance amongst midwifery educators to adopt such programmes [18].…”
Section: Introductionmentioning
confidence: 99%
“…To facilitate this, sectors like pharmacy and dentistry have seen a growth in research into the issues surrounding digital professionalism [13,14]. The skills and professionalism required by nurses engaging online has more recently been explored [15,16], and training introduced to pre-registration programmes [17]. However, there is reluctance amongst midwifery educators to adopt such programmes [18].…”
Section: Introductionmentioning
confidence: 99%
“…It is essential for nursing students to learn what it means to be a nurse during their education. [23] Alharbi, et al (2020) used a descriptive qualitative approach in small sample of sixteen undergraduate nursing students and found that social media use provides nursing students with an opportunity to learn more about the nursing profession, adopt an identity where students feel a sense of belonging and pride within the profession, and aids in the retention of nursing students. [8] Furthermore, students expressed their ability to influence society's view of the profession using social media as a medium, and share experiences among nursing colleagues.…”
Section: Professional Identitymentioning
confidence: 99%
“…However with the increasing incorporation of technology into the nursing practice, "e-professionalism" or digital professionalism is equally as important. [23] While nursing students often self-assess their social media skills as proficient for personal use, there is less opportunity to refine professional social media skills as educational programmes often do not offer this activity. [6] It is essential to prepare the nursing profession with the tools to actively engage in social media within this digital world.…”
Section: Professionalismmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Advantages of using social media for nursing students included developing professional networks, engaging in the nursing community, accessing and providing support, and enhancing their knowledge. 3 However, with the widespread usage of social media by registered nurses and nursing students, it has given risk to concerns about privacy-related risks and online professionalism. 4,5…”
Section: Introductionmentioning
confidence: 99%